CRITICAL FACTOR PEMBELAJARAN HYBRID PADA MASA PANDEMI COVID-19 - Ashadi, Firman (JP (Jurnal Pendidikan) : Teori dan Praktik, 2022)
Hybrid learning is a solution implemented by educational institutions to solve system learning problems during the Covid - 19 pandemic, namely system learning that gives students the ability to interact with their classmates on certain days and study from home on other days. However, the application of hybrid learning that is not accompanied by careful planning will not be a good solution, it will even make the problem more complicated. This study aims to describe the factors that can influence the effectiveness of implementing hybrid learning based on the results of a literature study. The research method used in this study is a literature study, where the author will examine previous studies related to the research topic, then it will be analysed and concluded. The results of this study indicate that there are several factors that influence the implementation of hybrid learning during the Covid-19 pandemic from various different research results, which need to be considered by educational institution managers before implementing hybrid learning. However, more in-depth research is needed regarding each factor to determine its impact on actors and the educational environment.